A Second Life German Cinema's First Decades - Elsaesser, Thomas (Film Culture in Transition, 1996)
German cinema is best known for its art cinema and its long line of outstanding individual directors. The double spotlight on these two subject has only deepened the obscurity surrounding the popular cinema. A Second Life performs a kind of archaeology on a period largely overlooked: the first two decades of German cinema. This collection of essays by established authors refocuses the terms of a debate that will develop in the years to come concerning the historical and cultural significance of popular cinema in Wilhelmine Germany.